2021
DOI: 10.1371/journal.pone.0247832
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-associated pneumonia among ICU patients in WHO Southeast Asian region: A systematic review

Abstract: Ventilator-associated pneumonia (VAP) is one of the most frequent ICU-acquired infections and a leading cause of death among patients in Intensive Care Unit (ICU). The South East Asian Region is a part of the world with limited health resources where infectious diseases are still underestimated. We aimed to review the literature in this part of the world to describe incidence, mortality and microbiological evidence of VAP and explore preventive and control strategies. We selected 24 peer-reviewed articles publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 57 publications
1
23
0
1
Order By: Relevance
“…VAP itself deals with resistant pathogens, and use of broad-spectrum antibiotics for its control further aggravates the condition. In a systematic review of VAP in south-east Asian countries, the incidence of VAP ranges from 2.13 to 116 per thousand ventilator days [ 7 ]. According to the systemic meta-analysis of the incidence of adult VAP in Asian countries (2018), Nepal has VAP incidence density of 21.4 per 1000 ventilator days and period prevalence of 21.7% [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…VAP itself deals with resistant pathogens, and use of broad-spectrum antibiotics for its control further aggravates the condition. In a systematic review of VAP in south-east Asian countries, the incidence of VAP ranges from 2.13 to 116 per thousand ventilator days [ 7 ]. According to the systemic meta-analysis of the incidence of adult VAP in Asian countries (2018), Nepal has VAP incidence density of 21.4 per 1000 ventilator days and period prevalence of 21.7% [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ventilator associated pneumonia is prominent in the ICU amongst device infections and has been well documented. 8,9,10,44,45 Catheter associated UTI was the second commonest device associated infection in this study. Majority of ICU admitted patients would need catheterization for reason of quantifying the urinary output, but the stroke patient is especially likely to be catheterized.…”
Section: Enterobacter Sakazakii Escherichia Coli Klebsiella Pneumonia Proteus Mirabilismentioning
confidence: 56%
“…Tracheal tubes and appliances are commonly contaminated by microorganisms, such as E. coli, S. aureus , [ 47,48 ] and C. albicans forming biofilms [ 49 ] capable of causing recurrent lung infections. [ 47,50 ] The resistance of intubated patients to antibiotics is more prominent in the presence of E. coli and S. aureus present in tubes and tracheal appliances. [ 48 ] Therefore, coping measures are necessary to treat infections caused by intubations.…”
Section: Resultsmentioning
confidence: 99%
“…RONS can cause an impact on intracellular components and the surrounding environment of cells that can be transported through the pores to the inner nucleus, increasing the amount of RONS in the cell with the consequent reduction in internal pH and oxidation of DNA, proteins, lipids, and carbohydrates. [ 50 ] Tian et al [ 54 ] showed a decrease in the membrane potential of S. aureus when the plasma jet above and below the water surface was used. They reported a reduction in the membrane potential of S. aureus depending on the time of plasma treatment.…”
Section: Resultsmentioning
confidence: 99%